2006
DOI: 10.1111/j.1479-8301.2006.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy Bodies (DLB) presenting with catatonic symptoms

Abstract: In this report, we demonstrate through a putative case that Dementia with Lewy Bodies (DLB) can present with a catatonic syndrome which can pose diagnostic and management challenges. The patient was an 88-year-old gentleman presenting with acute psychotic and catatonic symptoms on a background of 5 months of functional decline. He showed good response of catatonic symptoms to Clonazepam and psychotic symptoms to Olanzapine. This led to resolution of behavioral problems and the establishment of a putative diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Although catatonia is known to occur at any age, 3 the present case was unique in terms of the late age of presentation with Alzheimer's dementia and diabetes leading, which led to a diagnostic dilemma and problems with management. Catatonia occurring during the course of dementia has been reported with Lewy body dementia or in association with the use of donepezil in patients with Parkinson's disease 4 . A Medline‐based search using the key words ‘catatonia’ and ‘Alzheimer’ did not return any reports of cases similar to the present one.…”
Section: Discussionmentioning
confidence: 63%
“…Although catatonia is known to occur at any age, 3 the present case was unique in terms of the late age of presentation with Alzheimer's dementia and diabetes leading, which led to a diagnostic dilemma and problems with management. Catatonia occurring during the course of dementia has been reported with Lewy body dementia or in association with the use of donepezil in patients with Parkinson's disease 4 . A Medline‐based search using the key words ‘catatonia’ and ‘Alzheimer’ did not return any reports of cases similar to the present one.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, in 98 patients over 65 years of age admitted to the psychiatric ward of a general hospital, Takács et al ( 17 ) found a prevalence of catatonia in 17% of the cases, most of which were due to a general medical condition. Because catatonic symptoms are commonly found in certain types of primary neurodegenerative dementias [e.g., Lakshmana et al ( 18 ); Ishmora et al ( 19 )], it is surprising that dementia was not particularly associated with catatonia in either study. The reasons for this are unclear, but physicians' lack of familiarity with the manifestations of catatonia may be a sufficient explanation in most cases.…”
Section: Introductionmentioning
confidence: 78%
“…Neurological disorders: Dementia: Catatonia has been described in all dementia types, with reports in patients with Alzheimer’s disease (AD)[ 41 - 43 ]; frontotemporal dementia (FTD)[ 44 - 49 ]; dementia with Lewy bodies (DLB)[ 50 - 55 ]; and other cases with mixed, vascular, or nonspecified dementia[ 56 , 57 ]. Two prospective studies in psychogeriatric units reported a high prevalence of catatonia in patients with dementia using DSM-5 criteria, at 35.3%[ 16 ] and 42.8%[ 11 ].…”
Section: Resultsmentioning
confidence: 99%